Contribution to the study of faecal sludge as a resource for the city and province of Kinshasa in the Democratic Republic of the Congo - Kawata, Papy D.; Inkoto, Clément Liyongo; Pwema, Victor; Kibal, Irène; Kitadi, Jules M.; Mimbwete, Munanasi; Musibono, Dieu-donné E. A. (Orapuh Journal, 2024)
IntroductionSelf-contained sanitation systems such as septic tanks, latrines, and public toilets store faecal sludge, which must be regularly evacuated. If this sludge is not regularly collected, transported, and treated in a wastewater treatment plant, it can cause serious harm to the environment and public health.PurposeThis study aimed to show that the biosolids resulting from the treatment of septage collected in Kinshasa in the Democratic Republic of the Congo are uncontaminated and contain nutrients and properties that make them a resource to be valorized.MethodsThe present study was carried out in Kinshasa between January and March 2022. Samples of fresh faecal sludge were taken at Ndolo/auto service, a site where tanker trucks dump sludge from all over the city into a stream that flows into the Congo River. Pathogen levels were detected by counting bacteria. Helminth eggs were identified following the US Environmental Protection Agency's "Rule 503" recommendations for Class A and B biosolids. Total nitrogen was determined by the Kjeldahl method, while phosphorus and potassium were determined spectrometrically. Statistical analyses were performed using Excel 2021 and SPSS v.21 software.ResultsThe results obtained showed values <103 for all germs tested: E. coli, faecal coliforms, total coliforms, streptococci, and staphylococci in GS, MC, and Sabouraud media. No active helminth eggs were found. The results of this study showed that treated sludge contains major nutrients such as nitrogen, phosphorus, and potassium (NPK). Nitrogen content ranged from 1.2 mg/Kg to 7.6 mg/Kg, phosphorus from 2 mg/Kg to 3.2 mg/Kg, and potassium from 0.2 mg/Kg to 0.6 mg/Kg. These distributions show that over 95% of the levels of each element are within the confidence zone and indicate a strong correlation between the values of the different biosolids samples.ConclusionThe analyses carried out have shown that sewage sludge obtained from unplanted drying beds in Kinshasa offers very appreciable average nutrient values, which can be used in agriculture and in the rehabilitation of mining sites.